2022
DOI: 10.1111/jonm.13572
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the subfactors of self‐compassion on burnout among hospital nurses: A cross‐sectional study in South Korea

Abstract: Aim This study aimed to identify the effects of the subfactors of self‐compassion on hospital nurse burnout and provide basic knowledge for an intervention programme to prevent nurse burnout. Background Burnout in nurses has been reported to influence their own and patients' mental health and safety. Enhancing self‐compassion can help to prevent burnout. Methods This study involved descriptive research using a cross‐sectional design. Data were collected at H University Hospital in Korea, from January to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Em relação às facetas positivas de autocompaixão, os participantes apresentaram maior média na faceta mindfulness e, na faceta negativa, a autocrítica computou maior valor nesta métrica descritiva. Estes achados representam aspectos de promoção do bem-estar psicológico (Zessin et al, 2015) e reduz a probabilidade de esgotamento profissional (Jang et al, 2022). Ser consciente e aceitar as experiências negativas, por meio da atenção plena, minimiza a reatividade emocional (Roemer et al, 2015).…”
Section: Considerações Finaisunclassified
“…Em relação às facetas positivas de autocompaixão, os participantes apresentaram maior média na faceta mindfulness e, na faceta negativa, a autocrítica computou maior valor nesta métrica descritiva. Estes achados representam aspectos de promoção do bem-estar psicológico (Zessin et al, 2015) e reduz a probabilidade de esgotamento profissional (Jang et al, 2022). Ser consciente e aceitar as experiências negativas, por meio da atenção plena, minimiza a reatividade emocional (Roemer et al, 2015).…”
Section: Considerações Finaisunclassified
“…Teachers are in a context where they must manage and sometimes suppress their emotions, not only in their relationships with children but also with parents; thus, their self-compassion can be a factor in protecting their mental health. In a study of nurses in Korea, strengthening self-compassion helped prevent burnout ( Jang et al, 2022 ); and another study of college students in the United States also found that self-compassion mediated the relationship between narcissism and burnout ( Barnett and Flores, 2016 ). However, few if any studies on self-compassion in early childhood teachers exist, and none were found that consider teacher efficacy and burnout, which are important variables for early childhood teachers.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of previous research suggest that fostering coping strategies such as confidence and motivation may be useful for avoiding burnout (Pires & Ugrinowitsch, 2021). Enhancing selfcompassion has also been identified as a strategy to prevent burnout (Jang et al, 2022). Individuals with high levels of emotional intelligence may be protected from developing burnout, as they possess more effective coping strategies that enable them to be more resilient and manage stress better (Shahid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%